Activity and outcomes from a dedicated pleural on-call service - Asciak, R; Hallifax, R; Mercer, R; Hassan, M; Bradley, C; Corcoran, J; Wrightson, J; Psallidas, I; Rahman, N (Elsevier, 2018)
Pleural disease is increasing in frequency and is associated with more specialist evidence-based treatments. Over the last 5 years, the Oxford Pleural Unit has operated a pleural on-call service by instituting the provision of a pleural phone and e-mail service as a central point of contact for pleural-related questions, internally for the hospital trust, and externally for local general practitioners and district nurses. The phone is held during working hours, and the e-mail service is monitored daily by a member of the pleural team (consultants or pleural fellows).